The Effect of Eccentric Activity on Glucose Transporter Type 4 in Gastrocnemius Muscle of Streptozotocin-induced Diabetes Mellitus Mice - Adelia Handoko; Bambang Purwanto; Arifa Mustika (Journal of Agromedicine and Medical Sciences, 2017)
Diabetes mellitus (DM) is a metabolic disorder with increasing mortality rate. Decrease in GLUT-4 levels was found in diabetics resulting in an increase in postprandial blood glucose levels. Various innovative treatment have been developed, one of them is exercise. Exercise is growing fast today, especially eccentric contraction based exercise that potentially increase GLUT-4 muscle’s level. The aim of the present study was to investigate the effect of eccentric activity on glucose transporter type 4 in gastrocnemius muscle of streptozotocin-induced diabetes mellitus mice. Diabetic mice were grouped randomly into 2 groups. One group was given single bout of eccentric excercise by downhill running on 10o degree decline treadmill and the other group was given eccentric activity by downhill running on 0o degree. The GLUT-4 muscle’s level were measured after treadmill. Data obtained from each group were then analyzed using independent t-test, significant results were found (p<0.05). The conclusion of this study is single bout eccentric downhill running activity with 10o angel increases the levels of GLUT-4 muscles. Key words: Glucose Transporter Type 4, eccentric, Diabetes Mellitus, Muscle